Strategi Adaptasi Perusahaan Logistik terhadap Gangguan Rantai Pasok akibat Kenaikan Harga BBM: Studi Kasus Perusahaan Angkutan Barang di Provinsi Banten - Sandopart, Dewa Putu Yohanes Agata L. (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2024)
This study aims to explore the adaptation strategies developed by freight transportation companies in Banten Province in response to supply chain disruptions caused by the fuel price hike in September 2022. This study employs a qualitative approach with a case study design and involves six freight transportation companies selected through purposive sampling. Data were collected through in-depth interviews, passive participant observation, and document analysis, and analyzed using thematic analysis. The findings identify three main adaptation strategies, including cost-based operational efficiency through route optimization and preventive fleet maintenance, financial and relational adaptation through gradual tariff negotiation and customer base diversification, and collaborative strategies through inter-firm fleet sharing and the utilization of industry association roles. The novelty of this research lies in identifying horizontal collaboration practices as a specific adaptive capability in the context of land transportation in Indonesia, extending the vulnerability and capability factors framework. This study contributes to the development of supply chain resilience theory in the logistics sector of developing countries and provides practical recommendations for company management, industry associations, and policymakers.